LITERATUR REVIEW PENGARUH RELAKSASI OTOT PROGRESIF TERHADAP KUALITAS TIDUR PASIEN HEMODIALISA - Gusyam, Rival Maulana (SENTRI: Jurnal Riset Ilmiah, 2024)
Chronic Kidney Failure sufferers experience sleep quality problems. Progressive muscle relaxation is useful for improving the sleep quality of hemodialysis patients. Objective: This literature review aims to determine the description of progressive muscle relaxation on the sleep quality of hemodialysis patients. Method: Search for research journals or literature studies via Google Scholar, PubMed, Science Direct and Springer pages published from 2018-2023. Then select, analyze and review several sources. Results: Progressive muscle relaxation affects the sleep quality of chronic kidney failure patients undergoing hemodialysis. Conclusion: Progressive muscle relaxation can be used to improve the sleep quality of hemodialysis patients. Suggestion: Patients undergoing hemodialysis can apply progressive muscle relaxation to improve sleep quality.